Dynamics of Ministerial Change and Curriculum Rotation Analyzing Indonesian Education Policy through Literature Study - Nasywaa Hadaina Sabila Husnan; Inayah Dwiwanti Sya'rani; Gibran Sidik Abdussalam; Elis Sofiah (Social Impact Journal, 2025)
This study analyzes the pattern of the relationship between the change of education minister and changes in the national curriculum in Indonesia over the last 10-15 years. The purpose of this study is to analyze the pattern of the relationship between the change of education minister and changes in the national education curriculum in Indonesia, identify the impact of frequent curriculum changes due to political dynamics, and explore other driving factors of curriculum changes based on literature review. Through a qualitative approach with a literature review method, this research examines the "change of minister change of curriculum" phenomenon that has become a unique characteristic of the Indonesian education system. The results show that the change of education minister is consistently followed by the initiation of curriculum changes, starting from KTSP 2006, Curriculum 2013, to Merdeka Curriculum 2022. The impacts of these frequent curriculum changes include implementation confusion at the school level, the burden of repeated teacher adaptation and the instability of the education system as a whole. Factors influencing curriculum changes include political considerations, the results of international evaluations such as PISA, the demands of the times and the personal vision of the new minister. This study recommends the need for long-term policy consistency and in-depth evaluation before making curriculum changes.